Paraspinal muscle parameters predict postoperative sagittal balance in cervical disc arthroplasty: a structural equation model analysis - He, Junbo; Wu, Tingkui; Liu, Zijiao; Wu, Zhaodian; Wang, Xingjin; Wang, Beiyu; Huang, Kangkang; Hong, Ying; Li, Yong; Ding, Chen; Liu, Hao (Spine, 2026)
Study Design.  - Retrospective analysis. - Objective.  - To identify the associations between preoperative paraspinal muscle parameters and postoperative outcomes following cervical disc arthroplasty (CDA), while screening for predictors. - Summary of Background Data.  - Paraspinal muscles play a critical role in maintaining cervical alignment, significantly contributing to cervical mobility and stability. To date, there is limited evidence regarding the impact of paraspinal muscles on CDA. - Materials and Methods.  - This study included 185 patients who underwent single-level CDA. Preoperative paraspinal muscle parameters, including fatty infiltration (FI), cross-sectional area ratio (CSA r), and muscle asymmetry (ASY%), were assessed using MRI. Correlation analysis was employed for preliminary screening. Finally, structural equation modeling (SEM) was employed for comprehensive analysis. - Results.  - Paraspinal muscle degeneration was prevalent in this cohort, with a higher proportion of moderate to severe FI (Goutallier Grade > 2) from the cranial to caudal levels. According to the correlation analysis, at the final follow-up, cervical lordosis was most strongly correlated with CSA r at C4/5 (P=0.010); SVA was most related to CSA r at C5/6 (P=0.030); and the T1 slope was associated with CSA r at C4/5 (P<0.001), C5/6 (P<0.001), as well as at the surgical level (P<0.001). Moreover, a positive correlation was observed between preoperative pain scores and FI (P=0.035). However, no such correlation was identified in the postoperative period. Comparative analysis of SEMs across different muscle variables revealed variations in predictive factors for postoperative sagittal balance parameters, with CSA r emerging as the significant contributor (P=0.019, estimate=0.176), rather than FI or ASY%. - Conclusions.  - Compared with postoperative clinical outcomes, mobility, and prosthesis stability, preoperative muscle parameters were most correlated with sagittal balance after CDA. Specifically, CSA r outperformed in predicting postoperative sagittal balance. These findings suggest CDA may be associated with an elevated risk of sagittal imbalance when performed on patients with significant preoperative muscle degeneration. - Level of Evidence.  - Level 3.
Veröffentlicht: 15. Januar 2026
Gesehen am 09.02.2026